Opioid-overdose laws association with opioid use and overdose mortality. (November 2018) - McClellan, Chandler; Lambdin, Barrot H.; Ali, Mir M.; Mutter, Ryan; Davis, Corey S.; Wheeler, Eliza; Pemberton, Michael; Kral, Alex H.
Abstract: Introduction: Since the 1990's, governmental and non-governmental organizations have adopted several measures to increase access to the opioid overdose reversal medication naloxone. These include the implementation of laws that increase layperson naloxone access and overdose-specific Good Samaritan laws that protect those reporting overdoses from criminal sanction. The association of these legal changes with overdose mortality and non-medical opioid use is unknown. We assess the relationship of (1) naloxone access laws and (2) overdose Good Samaritan laws with opioid-overdose mortality and non-medical opioid use in the United States. Methods: We used 2000–2014 National Vital Statistics System data, 2002–2014 National Survey on Drug Use and Health data, and primary datasets of the location and timing of naloxone access laws and overdose Good Samaritan laws. Results: By 2014, 30 states had a naloxone access and/or Good Samaritan law. States with naloxone access laws or Good Samaritan laws had a 14% (p = 0.033) and 15% (p = 0.050) lower incidence of opioid-overdose mortality, respectively. Both law types exhibit differential association with opioid-overdose mortality by race and age. No significant relationships were observed between any of the examined laws and non-medical opioid use. Conclusions: Laws designed to increase layperson engagement in opioid-overdose reversal were associated with reduced opioid-overdose mortality. We found no evidence that these measures were associated with increased non-medical opioid use. Highlights: We conducted a national study of the impact of naloxone access and overdose Good Samaritan laws on opioid overdose deaths. Naloxone access and Good Samaritan laws are associated with 14% and 15% reductions, respectively, in opioid overdose deaths. Among African-Americans, naloxone and Good Samaritan laws reduce opioid overdose deaths by 23% and 26% respectively. Neither of these harm reduction measures result in increases in non-medical opioid use. These measures should be considered an important component of the strategy used to address the opioid overdose epidemic.